A Frailty Index from Next-of-Kin Data: A Cross-Sectional Analysis from the Mexican Health and Aging Study. (19th April 2017) - Pérez-Zepeda, Mario Ulises; Cesari, Matteo; Carrillo-Vega, María Fernanda; Salinas-Escudero, Guillermo; Tella-Vega, Pamela; García-Peña, Carmen
Abstract : Objectives. To construct a frailty index from next-of-kin information of the last year of life of community-dwelling 50 years old or older adults and test its association with health services utilization. Methods. Cross-sectional analysis from next-of-kin data available from the last wave of the Mexican Health and Aging Study (MHAS). Measurements. Along with descriptive statistics, the frailty index (FI) was tested in regression models to assess its association with adverse outcomes previous to death: number of hospitalized days in the previous year and number of visits to a physician in the previous year, in unadjusted and adjusted models. Results. From a total of 2, 649 individuals the mean of age was 74.8 (±11.4) and 56.3% ( n = 1, 183) were women. The mean of the FI was of 0.279 (±SD 0.131, R = 0.0–0.738) and distribution was biased to the right. There was a significant association ( p < 0.001) between the FI and number of hospitalized days ( β = 45.7, 95% CI 36.1–55.4, p < 0.001) and for the number of visits to a physician ( β = 25.93, 95% CI 19.27–32.6, p < 0.001) both models adjusted for age and sex. Conclusion. The FI constructed with next-of-kin data showed similar characteristics to similar indexes of older adults. It was independently associated with health care use.